Post-Transition Metals - Muzibur Rahman, Mohammed; Mohammed Asiri, Abdullah; Khan, Anish; Tabbakh, Thamer (IntechOpen, 2021)
Post-Transition Metals compiles information on synthesis, properties, characterization, and potential applications of post-transition metals such as indium and gallium. These metals are important for their optical, structural, morphological, and electronic properties. This book provides an overview of the history as well as the physical, structural, optical, and chemical properties of post-transition elements. It also discusses methods for the detection and separation of these metals, including special methods for determining their presence in industrial and organometallic products. The information contained herein is useful for physicists, researchers, chemists, materials engineers, and students.